Tracking presidents and policies: environmental politics from Lula to Dilma. (4th May 2017) - Hochstetler, Kathryn
ABSTRACT: Does the Brazilian presidential system shape environmental policy there? The comparative literature on environmental policy offers few reasons to think that it might. Most explanations of variations in the quantity and quality of environmental regulation stress levels of economic development or move outside of the nation-state to examine international processes of diffusion and convergence. Other studies look at large macrostructural differences like the contrast between democratic and authoritarian systems and/or the role of non-state actors. This article examines environmental policies and outcomes in three successive presidential administrations in Brazil to develop hypotheses about whether institutional factors should gain a larger place in comparative studies of environmental policies and outcomes.